Comparative Genomics of Ralstonia solanacearum Identifies Candidate Genes Associated with Cool Virulence - Bocsanczy, Ana M.; Huguet-Tapia, Jose C.; Norman, David J. (Frontiers in Plant Science, 2017)
Strains of the Ralstonia solanacearum species complex in the phylotype IIB group are capable of causing Bacterial Wilt disease in potato and tomato at temperatures lower than 24°C. The capability of these strains to survive and to incite infection at temperatures colder than their normally tropical boundaries represents a threat to United States agriculture in temperate regions. In this work, we used a comparative genomics approach to identify orthologous genes linked to the lower temperature virulence phenotype. Six R. solanacearum cool virulent (CV) strains were compared to six strains non-pathogenic at low temperature (NPLT). CV strains can cause Bacterial Wilt symptoms at temperatures below 24°C, while NPLT cannot. Four R. solanacearum strains were sequenced for this work in order to complete the comparison. An orthologous genes comparison identified 44 genes present only in CV strains and 19 genes present only in NPLT strains. Gene annotation revealed a high percentage of genes compared with whole genomes in the transcriptional regulator and transport categories. A single nucleotide polymorphism (SNP) analysis identified 265 genes containing conserved non-synonymous SNPs in CV strains. Ten genes in the pathogenicity category were identified in this group. Comparisons of type 3 secretion system, type 6 secretion system (T6SS) clusters, and associated effectors did not indicate a correlation with the CV phenotype except for one T6SS VGR effector potentially associated with the CV phenotype. This is the first R. solanacearum genomic comparative analysis of multiple strains with different temperature related virulence. The candidate genes identified by this comparison are potential factors involved in virulence at low temperatures that need to be investigated. The high percentage of transcriptional regulators among the genes present only in CV strains supports the hypothesis that temperature dependent regulation of virulence genes explains the differential virulence phenotype at low temperatures. This comparison contributes to find new possible connections of temperature dependent virulence to the previously described complex regulatory system involving quorum-sensing, phenotype conversion (phcA), acyl-HSL production and responses to SA. It also added novel candidate T6SS effectors and useful detailed information about the T6SS in R. solanacearum.